2017
DOI: 10.1186/s40169-017-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics in cancers: opposing interactions between PPAR gamma and the canonical WNT/beta‐catenin pathway

Abstract: Cancer cells are the site of numerous metabolic and thermodynamic abnormalities. We focus this review on the interactions between the canonical WNT/beta‐catenin pathway and peroxisome proliferator‐activated receptor gamma (PPAR gamma) in cancers and their implications from an energetic and metabolic point of view. In numerous tissues, PPAR gamma activation induces inhibition of beta‐catenin pathway, while the activation of the canonical WNT/beta‐catenin pathway inactivates PPAR gamma. In most cancers but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 174 publications
(185 reference statements)
1
58
0
Order By: Relevance
“…Several studies have shown that aerobic glycolysis is induced by overactivation of the WNT/β-catenin pathway through a direct activation of PDK1 and MCT-1 [ 31 , 35 , 96 , 97 ]. β-catenin activation induces the expression of PI3K/Akt signaling [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that aerobic glycolysis is induced by overactivation of the WNT/β-catenin pathway through a direct activation of PDK1 and MCT-1 [ 31 , 35 , 96 , 97 ]. β-catenin activation induces the expression of PI3K/Akt signaling [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvic acid could enter the TCA cycle and be completely oxidized in aerobic conditions, or could become lactic acid under anaerobic conditions [46,47]. HIF-1α could prevent the production of ATP and thus regulate the glycolysis of mouse granulosa cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…There have various metabolic pathway to produce pyruvic acid [43]. Pyruvic acid could enter the TCA cycle to be completely oxidized in aerobic condition, whereas it could become lactic acid under anaerobic oxygen condition [44,45]. HIF-1α could prohibit the production of ATP and thus regulate the glycolysis of mouse granulosa cells [46].…”
Section: Discussionmentioning
confidence: 99%